Physical Quality and Sun Protection Factor Value of The Sunscreen Lotion Extract of Carrot (Daucus carota L.) - Jamilatun, Makhabbah; Indah Lukito, Pradea; Angraini Saputri, Melisa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Sunlight does not always have a beneficial effect, the content of ultraviolet rays contained in it can harm the skin. Sunscreen is a substance that can protect the skin from exposure to ultraviolet (UV) rays. Carotenoids, provitamin A is one of the many natural antioxidants found in carrots. The purpose of this study was to determine the physical quality and SPF value of carrot extract sunscreen lotion (Daucus carota L), with the amount of carrot extract added as much as 10%. The research method used is quantitative experimental. The stages of the research included making Simplicia and making carrot extract, formulation and making carrot extract lotion, and testing the physical quality and SPF value of carrot extract lotion preparations. The results of the physical quality test for carrot extract lotion preparations, organoleptic, were yellow, smelled of oranges, and had a soft texture; pH of 7.59; spreadability of 5.5 cm; adhesiveness of 1.38; viscosity of 9990 cps; and an SPF value of 6.67. The conclusion from this study is that the physical quality of the carrot extract sunscreen lotion meets the standards, with the SPF value obtained classified as extra protection sunscreen.